'Like Playing With Fire Under a Hut' - You Will Get Burnt If You Do Not Adjust: Reflections of Social Work Students on Adjusting to University Life - Sibanyoni, Nkosinathi; Pillay, Roshini (Critical Studies in Teaching and Learning, 2023)
High dropout rates in first year and the enculturation into the academic literacies essential in promoting a successful academic adjustment are some of the challenges faced by many students when entering a higher education institution. The study aimed to understand some of the factors that contribute to student adjustment as social work students negotiate the higher education landscape from first to second year. The study explored the views of twelve first-year and seven second-year students utilising a qualitative research design where purposive sampling was used to recruit two focus groups. The results revealed that what both sets of students recognised as beneficial to their academic adjustment were the familiarisation of context, the use of effective time management skills, and positive attitudes. However, university-driven interventions aiming at assisting first year social work students with their academic life, such as the First Year Experience (FYE), were identified as too generic and not able to meet the unique needs of the participants. Recommendations emanating from the study included the development of discipline-specific academic development programmes that encourage social and academic adjustment. Additionally, collaboration between students within professional disciplines and the use of technology-enhanced learning could facilitate student adjustment.